Detection of Biofilm Genes (gtf) in Streptococcus mutans Isolated from Human Dental Caries - S. Flayyih, Adhraa; H.Hassani , Hayfa; H. Wali, Mohammed (Iraqi Journal of Science, 2023)
Sixty samples from saliva and dental plaque were selected from patients with caries active at ages from 4-65years. 22 isolates belong to Streptococcus mutans. All isolates pronounced adhesion and biofilm formation in various degrees. By using Polymerase Chain Reaction ﴾PCR﴿ Techniques, it was found that these isolates had gtfB encode GtfB with 80 bp, gtfC encode GtfC with 81 bp, and gtfD with 324 bp which explain their potential of biofilm formation.